Circulating Sex Steroid Measurements of Men by Mass Spectrometry Are Highly Reproducible after Prolonged Frozen Storage. Issue 197 (March 2020) - Handelsman, D.J.; Desai, R.; Seibel, M.J.; Le Couteur, D.G.; Cumming, R.G.
Graphical Abstract: Highlights: Reproducibility of steroid measurement in long-term frozen storage is crucial for long-term epidemiological research studies. Using liquid chromatography mass spectrometry serum testosterone, dihydrotestosterone estradiol and estrone were highly reproducible after 10 years unthawed frozen storage as well as after multiple freeze-thaw cycles, apart from small increases in serum estradiol. Abstract: Long-term studies investigating hormone-dependent cancers and reproductive health often require prolonged frozen storage of serum which assumes that the steroid molecules and measurements are stable over that time. Previous studies of reproducibility of circulating steroids have relied upon flawed historical rather than contemporaneous controls. We measured serum testosterone (T), dihydrotestosterone (DHT), estradiol (E2) and estrone (E1) in 150 randomly selected serum samples by liquid chromatography-mass spectrometry (LC-MS) from men 70 years or older (mean age 77 years) in the CHAMP study. The original measurements in 2009 were repeated 10 years later using the identical serum aliquot (having undergone 2-4 freeze-thaw cycles in the interim) in 2019 together with another never-thawed aliquot of the same serum sample. The results of all three sets of measurements were evaluated by Passing-Bablok regression and Bland-Altman difference analysis. Serum androgens (T, DHT) and estrogens (E2, E1) measured by LC-MS display excellent reproducibility when stored for 10 years at -80 C without thawing. Serum T and DHT displayed high level of reproducibility across all three sets of measurements. Multiple freeze-thaw cycles over those storage conditions do not significantly affect serum T, DHT and E1 concentrations but produce a modest increase (21%) in serum E2 measurements.